Effect of anthelmintics upon host organism - THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ), Y.; FRYDAS (Σ. ΦΡΥΔΑΣ), S.; RIZOS (Η. ΡΙΖΟΣ), E. (Journal of the Hellenic Veterinary Medical Society, 2018)
To be estimated the effects of anthelmintics to the host, 21 female sheep of various age, breed and weight, which were naturally infected with gastrointestinal nematodes, were used. These animals were divided into three groups and given per os: in the 1st group, which was composed of 7 sheep, Morantel citrate (tetrahydropyrimidine group) approx. 465 mg/b.w., in the 2nd, which was composed of 8 sheep, Albendazole (benzimidazole group) approx. 300 mg/b.w. and in the 3rd, which was composed of 6 sheep, tap water only and this group was used as control. From these animals, blood samples intrajagularly were taken, at the same day, once a week for 9 continuous weeks. The first blood sample was taken 4 weeks before the anthelmintic therapy and the last one 5 weeks after therapy. There were no significance diferences (p> 0,005) in pre- and posttherapy measurements, regarding the PCV,s in all groups. In the control and morantel citrate groups, the leucocyte volume remained static, while contrarily, in the albendazole group a significance difference (p< 0,005) were observed. Because, the albendazole inhibits the construction of intestine cell microtubules of parasites, it can be concluded that, this activity, effects the host cells, and thus, this reduction of leucocytes was observed.